Use of an Educational Module to Improve Confidence and Knowledge of Celiac Disease Among Nurse Practitioners in Pennsylvania: A Quasi-Experimental Mixed-Methods Design. (September 2018) - Elkin, Aleda; Grant, Catherine; Coleman, Timothy; Sereika, Susan M.
Abstract : Accurate and prompt diagnosis of celiac disease has proven difficult due to the myriad of presenting symptoms and a lack of a clear diagnostic protocol. This pilot study investigated the use of an evidence-based multimedia educational module on nurse practitioner confidence and knowledge of celiac disease. Thirteen nurse practitioners in Pennsylvania completed all study activities, which involved the use of an online pretest, learning component, an immediate post-test, along with 2 follow-up surveys. Results revealed that nurse practitioner confidence ( p ⩽ .05) and knowledge ( p ⩽ .05) levels significantly improved after participation in the educational intervention. Qualitative data also revealed that nurse practitioners are more aware of the various presentations and symptoms of celiac disease and stated that with this knowledge, their clinical practice has changed to include recognition of the various celiac disease presentations. Findings suggest that nurse practitioners are now more knowledgeable of the various presentations of celiac disease and may be more likely to consider celiac disease as a diagnosis if patients present with typical or atypical symptoms. Abstract : Supplemental Digital Content is Available in the Text.